Grandchildren as Substitute Heirs in Indonesia’s Islamic Inheritance Law: Formulation and Implementation of the Compilation of Islamic Law - Muhammad Fadhlan Is; Dede Hafirman Said (Hukum Keluarga Islam IAIN LANGSA, 2025)
This study examines in depth the role and position of grandchildren in Islamic inheritance law in Indonesia, particularly in relation to Article 185 of the Compilation of Islamic Law (KHI), which regulates substitute heirs. Although the debate regarding this article has been widely discussed in previous research, most studies do not identify in detail the theoretical and practical gaps that arise in the application of Article 185 of the KHI, especially related to the influence of Hazairin's thinking and differences in interpretation in the field. This study aims to fill this gap by analyzing the history, formulation, and implementation of the provisions regarding substitute heirs in the KHI, as well as the contribution of Hazairin's theory to changes in the inheritance system in Indonesia. The method used is library research with a descriptive qualitative approach, which analyzes primary legal sources in the form of relevant legal texts, as well as secondary literature including books, scientific articles, and related journals, with technique content analysis to explore the meaning and implications of the provisions of Article 185 of the KHI and Hazairin's theory, as well as a comparative analysis to assess the suitability between theory, practice, and classical Islamic inheritance law. The results of the study indicate that Article 185 of the KHI which regulates substitute heirs has three main views, namely rejecting, accepting, and accepting with conditions for revision. This study contributes to understanding the theoretical and practical dimensions of the provisions of substitute heirs, as well as their implications for the formation of a more inclusive and equitable inheritance system in Indonesia. The practical implication is the need to revise the wording of Article 185 of the KHI to ensure consistency and fairness in its implementation, thereby providing better legal protection for heirs, especially grandchildren who have lost their parents.